Surface Conductivity and Preferred Orientation of TiN Film for Ti Bipolar Plate - Zhi Yan (Coatings, 2022)
The properties of thin films are often influenced by the crystal’s preferred orientation. In the present study, we report the strong dependence of surface conductivity on the preferred orientation of TiN film that acts as the coating material for Ti bipolar plate. The preferred orientation of TiN film is successfully controlled along the (111) or (200) planes by adjusting the N2 flow rate or Ti substrate temperature during the deposition process via DC (direct current) reactive magnetron sputtering. Small N2 flow rate of 3 to 6 sccm or low substrate temperature (e.g., 25 °C) facilitates the growth of TiN films along the (111). The (111) preferred orientated TiN films show much lower interfacial contact resistance (ICR) than the (200) preferred orientated films. A considerably low ICR value of 1.9 mΩ·cm2 at 140 N/cm2 is achieved at the N2 flow of 4 sccm and the substrate temperature of 25 °C.